Stories of Menacing Globalization: A Review of Two Books (American Journal of Islam and Society, 1998)
Susan Strange (1996) The Retreat of the State: The Drfision of Power inthe World Economy. New York, Ny: Cambridge University Press. 218pages. $16.95 paperback.Martin J. Beck Matustik (1998) Specters of Liberation: Great ReMals inthe New World Order Albany, Ny: State University of New York Press.360 pages. $23.95 paperback.In 1996, Philip Cerny wrote in the International Journal that globalizationliterature is a set of contested stories that frame the categories andconcepts informing public debate. Retreat and Specters tell such stories toshape perceptions of globalization as a threat demanding vigorous scholarlyattention and creative political responses. Both books depict globalizationas a frightening menace heralding social tumult; dislocation; “ayawning hole of non-authority” (Strange, p. 14); and a terrifying legacy of“economic immiseration, political oppression, cultural marginalization,and racial and ethnic cleansing” (Matustik, p. x). Strange outlines potentialthreats, leaving readers to conjure responses. Matustik seeks to openthe conceptual space necessary to craft alternative conditions, leavingreaders to specify the threats and imagine how to achieve alternatives.Neither author explains or analyzes globalization. Strange disdains globalizationas no more than empty jargon, and describes it as an economicand technological phenomenon with political consequences. Matustik considersit to be social with political and cultural consequences.Both authors address prevailing stories of globalization as much asglobal conditions. Each exhorts readers to confront globalization byexploring the gritty reality and actual conditions confronting individuals,rather than by accepting prevailing stories. Thus, each confirms Cerny’s claim (1996:260) that globalization is more significant as a contested discoursethan as an analytical literature or global condition. In this light, onedoes well to read Strange and Matustik as storytellers and to ask if theirinterpretive tales reflect one’s experiences and impressions of global life.Unsurprisingly, both authors tell only partial tales, but each poses worthyquestions ...